2021
DOI: 10.3390/ijerph18094982
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition in Elite Soccer Players from Youth to Senior Squad

Abstract: There is a strong relationship between body composition and performance in male soccer players. This study aimed to display an optimal body height and weight, and body composition profile of male soccer players for four competitive age groups. This cross-sectional study included four groups: U-15 (n = 152), U-17 (n = 154), U-19 (n = 61), and seniors (n = 27). Body height and weight were measured under standard conditions, and the bioelectrical impedance analyzer (BIA) analyzed body composition. On average, soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
(34 reference statements)
0
13
0
1
Order By: Relevance
“…Other studies have demonstrated that body fat percentage has a significant and negative correlation with age [18,40]. Players from professional U15, U17, and U19 soccer teams had 12.9 ± 6.8%, 10.0 ± 3.6%, and 10.4 ± 3.9% body fat, respectively [18], a fact that also occurs in other sports (e.g., basketball) [41].…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Other studies have demonstrated that body fat percentage has a significant and negative correlation with age [18,40]. Players from professional U15, U17, and U19 soccer teams had 12.9 ± 6.8%, 10.0 ± 3.6%, and 10.4 ± 3.9% body fat, respectively [18], a fact that also occurs in other sports (e.g., basketball) [41].…”
Section: Discussionmentioning
confidence: 89%
“…Other studies have demonstrated that body fat percentage has a significant and negative correlation with age [18,40]. Players from professional U15, U17, and U19 soccer teams had 12.9 ± 6.8%, 10.0 ± 3.6%, and 10.4 ± 3.9% body fat, respectively [18], a fact that also occurs in other sports (e.g., basketball) [41]. This fact would explain why our U12 players present a higher body fat percentage, perhaps because they had not fully matured to the point where adipose mass decreases and muscle mass increases [18].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations